Temperature-Dependence Corrosion Behavior of Ti6Al4V in the Presence of HCl - Yu, Fei; Addison, Owen; Davenport, Alison (Frontiers in Materials, 2022)
Ti alloys have been widely used in biomedical field due to good compatibility and corrosion resistance. However, corrosion-related failures of implanted Ti devices and prostheses have been regularly reported within the medical literature. The corrosion of Ti alloys has attracted much attention in vivo and in vitro. In the current study, the corrosion behavior of Ti6Al4V alloy was investigated using surface analysis and electrochemical tests. Corrosion of Ti6Al4V in 2 M hydrochloric acid is temperature dependent within the temperature range studied. It has found that the steady state current density at −510 mV vs. SCE (the primary passivation potential at the physiological temperature of 37°C) becomes higher with increasing temperature. The α phase of Ti6Al4V is preferentially dissolved relative to the β phase after potentiostatic measurement at primary passivation potential in 2 M HCl at 37°C. This investigation provides novel and useful information for Ti corrosion-related failures of biomedical implants and prostheses.